Geochemistry - René, Miloš; Aiello, Gemma; El Bahariya, Gaafar (IntechOpen, 2021)
Geochemistry includes new contributions to the field of granite rocks geochemistry, mineralogy, petrology and microstructure studies, geochemistry of radioactive isotopes, and geochronology. It contains detailed geochemical, mineralogical, petrological, sedimentological and geostructural studies from Europa, Asia, Africa, South America and Australia Chapters present geochemical exploration methods, isotopic studies, and macro- and microstructural analyses.